Caracterização acústica em baixas frequências de modelos retangulares e não retangulares de salas em escala reduzida - Russi, Dyhonatan Willian (2020)
Choosing the correct analysis methodology to study and design acoustic behavior at low fre- quencies, considering small non-rectangular rooms and critical listening rooms, can influence the auditory sensations that the user of the room will have when making use of the space. This research compares two methodologies that analyze low frequencies in small scale models, of possible rectangular and non-rectangular shapes, of acoustic rooms. Comparisons are made between the parameters T20, T30, EDT, C80, D50 and Ts, obtained in computational models that make use of the finite element method (FEM) and analytical calculation models that make use of the equations that describe the acoustic behavior of rectangular rooms with rigid walls. This research also evaluated, through Pearson’s correlation coefficient r, the similarity between the decay curves, in the form of the inverted cumulative integrals of the impulse responses (ICI), evaluated the similarity between the frequency response functions (FRF) and evaluated the si- milarity between the impulse responses (IR), obtained with these evaluation methodologies. The results indicate that the less rectangular the shape of the room is, smaller will be the simi- larity between the impulse responses obtained in the methodologies. This fact can influence, for example, the acoustic perception in a non-rectangular room designed using analytical mo- dels for rectangular rooms. The methodologies used in this research were validated with the measurement of a physical model built on a small scale, after identifying the convergence of results between the data obtained in the measurements, in the virtual models in FEM and in the analytical ones. All geometric shapes, of the possible acoustic rooms, were elaborated on a reduced scale, with a reduction ratio of (1: 8). The data obtained in these measurements were used as input data for other analyzes made by this research.